1995
DOI: 10.1002/cne.903580304
|View full text |Cite
|
Sign up to set email alerts
|

Colocalization of γ‐aminobutyric acid with vasopressin, vasoactive intestinal peptide, and somatostatin in the rat suprachiasmatic nucleus

Abstract: The seemingly contradictory observations in previous publications that gamma-aminobutyric acid (GABA) is detected in all cell bodies of the suprachiasmatic nucleus (SCN) and that terminals originating from the SCN are only 20-30% GABA positive prompted us to investigate whether this might be explained by a preference of colocalization in terminals of certain peptidergic neurons in the SCN or by a day/night rhythm in GABA synthesis. At three different circadian times, animals were perfusion fixed, and their SCN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
1
2

Year Published

1997
1997
2004
2004

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 46 publications
3
59
1
2
Order By: Relevance
“…6 D). In SCNs of Sprague-Dawley rats, Buijs et al (1995) also found that GABA\VIP colocalisation in boutons was about twice as frequent as GABA\VP colocalisation, al- though the overall occurrence of colocalisations reported for the rat was lower than that in the mouse. On the other hand, in SCNs of Wistar rats Tanaka et al (1997) reported that GABA colocalisation occurred in about 90 % of both VIP and VP-containing neurons.…”
Section: Gaba and Neuropeptidesmentioning
confidence: 82%
See 3 more Smart Citations
“…6 D). In SCNs of Sprague-Dawley rats, Buijs et al (1995) also found that GABA\VIP colocalisation in boutons was about twice as frequent as GABA\VP colocalisation, al- though the overall occurrence of colocalisations reported for the rat was lower than that in the mouse. On the other hand, in SCNs of Wistar rats Tanaka et al (1997) reported that GABA colocalisation occurred in about 90 % of both VIP and VP-containing neurons.…”
Section: Gaba and Neuropeptidesmentioning
confidence: 82%
“…2 B). The nature of the nuclear labelling in GABAergic neurons in the SCN is unclear, both in terms of the identity of the immunoreactive epitopes and the functional implications, as noted also by Buijs et al (1994Buijs et al ( , 1995. Nevertheless, similar marking of GABAergic nuclei in other parts of the brain is regarded as not understood rather than nonspecific (P. Somogyi, personal communication).…”
Section: Gabaergic Somatamentioning
confidence: 99%
See 2 more Smart Citations
“…Buijs et al (28) be an endocrine code of the environmental light-dark cycle conveying photic information that is used by an organism for both circadian and seasonal temporal organization (29-31) and it seems that there is no regular fluctuation in the pineal metabolism leading to melatonin synthesis and release throughout the estrous cycle in female rats (32,33). The SCN is also fundamental in the induction of renewed positive estrogen control of the preovulatory wave of LH, and melatonin may act together with the hypothalamus in altering the secretion of GnRH and the consequent production of gonadotropins (16).…”
Section: Discussionmentioning
confidence: 99%